Determination of the reference frames deflections from optical observations of GNSS satellites - Choliy, V.Ya.; Zhaborovskyy, V.P.; Taradiy, V.; Rykhlova, L. (Advances in Astronomy and Space Physics, 2011)
Optical observations of navigation satellites were carried out at Terskol observatory during 2007-2010 with the aim to determine the deffection angles between GPS and GLONASS dynamical reference frames. There were three different observations strategies: celestial equator crossing, intersection of visible satellite paths, occultation of astrometric stars with the satellite. We present methodology of observation, data processing and the first results.